Penggunaan Framework Laravel dalam Perancangan Sistem Informasi Persediaan dan Penjualan Obat di Toko Ayu Berbasis Web - Rohmat Taufiq; Dyas Yudi Priyanggodo; Safitri Wulandari; Yani Sugiani (Universitas Muria Kudus, 2025)
The maintenance process of machinery is very important for every company to carry out. The current system in the process of preparing machine maintenance reports in the JQA department of PT. Gajah Tunggal Tbk has not yet used a computerized system. Machine maintenance reports are still in paper form, which causes document accumulation, resulting in delays in data retrieval and potential damage or loss of documents. This study aims to design a machine maintenance report information system in the JQA department to address the existing problems. The data collection methods used are observation, interviews, and literature review, while the system analysis method employed is PIESCES (Performance, Information, Economic, Control, Efficiency, and Service). The system was designed using an object-oriented analysis method with Unified Modeling Language (UML) and was built using the Balsamiq application. The maintenance system was created using the PHP programming language and a MySQL database with the Xampp web server. The research results proved that this system successfully improved work efficiency and reduced errors in machine maintenance report data entry. Therefore, the system that was developed is expected to improve performance quality to become better.